„Comics making as a form of prayer?”. Komiksowa materialność na przykładzie komiksu Deserto / Nuvem Francisco Sousy Lobo - Jankowski, Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Francisco Sousa Lobo (Portugal) touches on religious themes in many of his comics. In real life, he has been both for and against Catholics, and now he prefers to watch the world from above, sitting on a high comic book wall. In the split-book Deserto/Nuvem, which I propose to analyse in this article, he decides to create a reportage about the Catholic Carthusian order from Évora: in Deserto he presents a record of a week spent among monks, and Nuvem consists of 20 letters written to a monk. I would like to look at these comics in response to the question with which Pedro Moura concluded the Deserto/Nuvem review – “Comic-making as a form of prayer?” and through the concepts of the materiality of the comic book (Aaron Kashtan Between Pen and Pixel. Comics, Materiality, and the Book of the Future) and the performativity of the act of experiencing the comic book (Ian Hague Comics and the Senses: A Multisensory Approach to Comics and Graphic Novels).